2016
DOI: 10.24200/sci.2016.2098
|View full text |Cite
|
Sign up to set email alerts
|

Flexural performance of RC beams strengthened by bonded CFRP laminates under monotonic and cyclic loads

Abstract: RC beams, strengthened by external bonded FRP reinforcement, often fail by one of several possible debonding modes. Although many experimental studies have been performed to assess the exural behavior and failure modes of FRP-strengthened RC beams under monotonic loads, the exural performance of these elements under cyclic loads have rarely been examined. The present paper illustrates the results of an experimental study aimed at better understanding of the structural behavior and debonding failure mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Saeidi-Moein et al [39] utilized EB technique to strengthen RC beams with CFRP laminates, and the behavior of the strengthened beams under monotonic and cyclic loadings was studied. The results showed that strengthening RC beams using CFRP laminates can increase the energy dissipation capacity (per cycle) until the FRP debonding occurs.…”
mentioning
confidence: 99%
“…Saeidi-Moein et al [39] utilized EB technique to strengthen RC beams with CFRP laminates, and the behavior of the strengthened beams under monotonic and cyclic loadings was studied. The results showed that strengthening RC beams using CFRP laminates can increase the energy dissipation capacity (per cycle) until the FRP debonding occurs.…”
mentioning
confidence: 99%